Differential Behavior of Eicosapentaenoic and Docosahexaenoic Acids on the Organization, Dynamics, and Fusion of Homogeneous and Heterogeneous Membranes - Joardar, Ankita (Langmuir : the ACS journal of surfaces and colloids, 2023)
Membrane fusion is a common course in innumerable biological processes that helps in the survival of eukaryotes. Enveloped viruses utilize this process to enter the host cells. Generally, the membrane lipid compositions play an important role in membrane fusion by modulating the membrane's physical properties and the behavior of membrane proteins in the cellular milieu. In this work, we have demonstrated the role of polyunsaturated fatty acids (PUFAs), such as eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids, on the organization, dynamics, and fusion of homogeneous and heterogeneous membranes. We have exploited arrays of steady-state and time-resolved fluorescence spectroscopic methods and polyethylene glycol-induced membrane fusion assay to elucidate the behavior of EPA and DHA on dioleoyl phosphatidylcholine (DOPC)/cholesterol (CH) homogeneous and DOPC/sphingomyelin/CH heterogeneous membranes. Our results suggest that EPA and DHA display differential effects on two different membranes. The effects of PUFAs in homogeneous membranes are majorly attributed to their flexible chain dynamics, whereas the ability of PUFA-induced cholesterol transfer from the lo to the ld phase rules their behavior in heterogeneous membranes. Overall, our results provide detailed information on the effect of PUFAs on homogeneous and heterogeneous membranes